2022
DOI: 10.1159/000520820
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of a Biomarker to Detect Contrast-Induced Acute Kidney Injury during Percutaneous Cardiovascular Procedures

Abstract: <b><i>Introduction:</i></b> Contrast-induced acute kidney injury (CI-AKI) is a major clinical complication of percutaneous cardiovascular procedures requiring iodinated contrast. Despite its relative frequency, practicing physicians are unlikely to identify or treat this condition. <b><i>Methods:</i></b> In a 2-round clinical trial of simulated patients, we examined the clinical utility of a urine-based assay that measures liver-type fatty acid-binding protein (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
1
0
4
Order By: Relevance
“…Results indicated that the inclusion of L-FABP was 2.9 times more likely to correctly identify patients’ risk for AKI and were more than twice as likely to treat for AKI by providing volume expansion and withholding nephrotoxic medications. The study showed the greatest clinical utility in the pre-procedure and peri-procedure settings but limited value in the post-procedure setting [ 117 ].…”
Section: Novel Biomarkers: the Necessity For A Precise Ci-aki Diagnosismentioning
confidence: 99%
“…Results indicated that the inclusion of L-FABP was 2.9 times more likely to correctly identify patients’ risk for AKI and were more than twice as likely to treat for AKI by providing volume expansion and withholding nephrotoxic medications. The study showed the greatest clinical utility in the pre-procedure and peri-procedure settings but limited value in the post-procedure setting [ 117 ].…”
Section: Novel Biomarkers: the Necessity For A Precise Ci-aki Diagnosismentioning
confidence: 99%
“…A LRA pós-contraste é considerada a terceira causa mais comum de LRA no ambiente hospitalar, ficando atrás da hipovolemia e dos medicamentos nefrotóxicos. É uma complicação frequente em procedimentos cardiovasculares percutâneos (7-18%), o que pode oferecer um custo adicional ao procedimento, assim como aumento na morbidade e mortalidade desses pacientes (PEABODY et al, 2022).…”
Section: Biomarcador Proteína De Ligação De áCidos Graxos Do Tipo Hep...unclassified
“…Caso seja detectada precocemente por biomarcadores, é possível identificar mais precisamente quais os pacientes vulneráveis e, dessa forma, atuar de forma profilática. No entanto, uma dificuldade enfrentada pelos cardiologistas intervencionistas é não conseguir prever o desenvolvimento de LRA pós-contraste pois a creatinina, principal biomarcador utilizado, não possui sensibilidade para medir declínios na TFG até que ocorra 50% de perda da função renal (PEABODY et al, 2022).…”
Section: Biomarcador Proteína De Ligação De áCidos Graxos Do Tipo Hep...unclassified
See 2 more Smart Citations